Mechanical and abrasive wear performance of titanium di-oxide filled woven glass fibre reinforced polymer composites by using Taguchi and EDAS approach - Chairman, Chelliah Anand (2021)
Two-body abrasive wear behavior of glass fabric reinforced (GC) epoxy and titanium dioxide (TiO₂) filled composites have been conducted out by using a tribo test machine. GC and TiO₂ filled GC composites were produced by the hand layup technique. The mechanical performances of the fabricated composites were calculated as per ASTM standards. Three different weight percentages were mixed with the polymer to develop the mechanical and abrasive wear features of the composites. Evaluation Based on Distance from Average Solution (EDAS), a multi-criteria decision technique is applied to find the best filler content. Based on the output, 2wt% TiO₂ filler gave the best result. Abrasive wear tests were used to compare GC and TiO₂ filled GC composites. The abrasion wear mechanisms of the unfilled and TiO₂ filled composites have also been studied by scanning electron microscopy. The outcome of the paper suggests the correct proportion of filler required for the resin in order to improve the wear resistance of the filled composites. Taguchi combined with Multi-Criteria Decision Method (MCDM) is used to identify the better performance of the TiO₂ filled epoxy composites.